The impact of call warrant listing on underlying stock returns: The Malaysian evidence - Yip, Yen Yen (2007)
This study analysis the impact of call warrant listing on its underlying stock’s returns by employing the event study methodology. The sample of study consists of 41 warranted stocks listed on Bursa Malaysia from March 2003 to March 2007. Overall; the results suggest that call warrant listing has no significant impact on its underlying stock’s returns. The outcome of this study is contradicting with those studies based on Western market, in which option listing will tend to improve the performance of the underlying market by producing positive abnormal returns. Such phenomenon infers that whilst call warrant provides an alternative to stock option, it does not expand the opportunity set of investors to the extent that stock option does. Finally, the relatively small free float in Malaysian market could be one of the contributing factors.